2015
DOI: 10.1021/pr501299m
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Phenotyping of an Adoptive Transfer Mouse Model of Experimental Colitis and Impact of Dietary Fish Oil Intake

Abstract: Inflammatory bowel diseases are acute and chronic disabling inflammatory disorders with multiple complex etiologies that are not well-defined. Chronic intestinal inflammation has been linked to an energy-deficient state of gut epithelium with alterations in oxidative metabolism. Plasma-, urine-, stool-, and liver-specific metabonomic analyses are reported in a naïve T cell adoptive transfer (AT) experimental model of colitis, which evaluated the impact of long-chain n-3 polyunsaturated fatty acid (PUFA)-enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…This might explain the differences of the HFD-induced reduced inflammation we observe between the two models. There are also discrepancies in the effectiveness of dietary intervention in colitis models using other dietary lipids [ 19 ]. Inconsistent findings of the effect of omega-3 fatty acids in different colitis models demonstrate that we need to study the effects of plant sterol or stanol in more depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might explain the differences of the HFD-induced reduced inflammation we observe between the two models. There are also discrepancies in the effectiveness of dietary intervention in colitis models using other dietary lipids [ 19 ]. Inconsistent findings of the effect of omega-3 fatty acids in different colitis models demonstrate that we need to study the effects of plant sterol or stanol in more depth.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent findings of the effect of omega-3 fatty acids in different colitis models demonstrate that we need to study the effects of plant sterol or stanol in more depth. Metabolomic analysis could help to get insights in possible molecular processes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both NMR and MS methods generate high density data, from which meaningful biological information are recovered using multivariate data analytical approaches [17,18]. Metabonomics has already begun to contribute to the field by generating key metabolic insights [1,19,20,21]. In the context of the study of pediatric subjects, metabonomics offers a unique opportunity to capture metabolic fingerprints of an individual using minimally invasive samples, such as blood spots or urine.…”
Section: Introductionmentioning
confidence: 99%
“…Many metabolites were found in several different sample types in both humans and animals, but not necessarily the same. For example, alanine was increased in serum [24] and feces [4,25] from humans and in colon [17] and plasma [26] from mice, but it was decreased in urine [43] and colon [35,36] in humans and serum [16] and urine [38] in animals, illustrating the differences observed for many metabolites (Supplementary Table S9). The highest similarity to human studies was observed with the acute DSS mouse model ( Supplementary Table S9).…”
Section: Differentiation Of Metabolites According To Key Experimentalmentioning
confidence: 95%